2002
DOI: 10.2307/972223
|View full text |Cite
|
Sign up to set email alerts
|

Getting Closer to the Source: Using Ethnoarchaeology to Find Ancient Pottery Making in the Naco Valley, Honduras

Abstract: The problem of finding the locations of ceramic production has limited interpretations of prehispanic Mesoamerican economies. A new method for locating pottery-making is offered that emphasizes ties between the process of clay extraction and the manufacture of ceramic goods at the same clay source. Observations at modern brick and roof tile-making factories (tejeras) in the Naco Valley, Honduras, show that an effective arrangement for intensive production of ceramic goods is to create the finished product at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Nonetheless, after many centuries of geological activity, the original source could potentially be buried under many meters of alluvium in this environment, and not be accessible today. Wherever the clay source was located, the site of polychrome production must have been near the source, as it has been shown that ceramics are often produced at clay sources themselves [8]. We hypothesize therefore that the locus of production for the majority of Early Nasca polychromes was within a 3e4-km radius (the ethnographic upper limit of clay transport) of where sample #CS029 was found.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, after many centuries of geological activity, the original source could potentially be buried under many meters of alluvium in this environment, and not be accessible today. Wherever the clay source was located, the site of polychrome production must have been near the source, as it has been shown that ceramics are often produced at clay sources themselves [8]. We hypothesize therefore that the locus of production for the majority of Early Nasca polychromes was within a 3e4-km radius (the ethnographic upper limit of clay transport) of where sample #CS029 was found.…”
Section: Discussionmentioning
confidence: 97%
“…Some ceramic vessels were fashioned at the Late Classic capital where at least one massive, stone-lined kiln measuring 6 m in diameter was built and used during the Terminal Classic (Urban et al, 1997). No comparably large facilities are known from the valley during the 9th through 10th centuries though evidence for ceramic production on a smaller scale is suggested by materials recovered from five rural sites (Connell, 2001). Obsidian blades were fabricated at 20 Terminal Classic households within La Sierra and its immediate vicinity, though during this interval there are signs of knapping from seven other settlements.…”
Section: Political Decentralization and Craft Dispersalmentioning
confidence: 99%
“…A 1.43 m-deep depression measuring 32 x 45 m lies on the site's northwest margin; Structure 24 overlooks and is built into the southeastern rim of this declivity (Figures 3 and 5). Excavations revealed that the pit was dug into extensive clay deposits during the early Terminal Classic, creating a borrow pit analogous in form and size to those associated with both modern and ancient ceramic manufacturing facilities in the Naco Valley (Connell 2002). Associated with the northwest depression was an unusually dense concentration of worked and used sherds, vessel fragments whose edges were rounded intentionally or through use.…”
Section: Craft Specializationmentioning
confidence: 99%